Cellular responses to individual amino‐acid depletion in antibody‐expressing and parental CHO cell lines. Issue 5 (11th December 2013) - Fomina‐Yadlin, Dina; Gosink, John J.; McCoy, Rebecca; Follstad, Brian; Morris, Arvia; Russell, Chris B.; McGrew, Jeffrey T.
ABSTRACT Depletion of two nonessential amino acids, asparagine (Asn) and glutamine (Gln), occurred during a fed‐batch production process with a CHO cell line expressing a recombinant antibody. This depletion coincided with growth suppression and the onset of the stationary phase. Experimental withdrawal of Asn led to cell cycle arrest of cell line A in G0/G1 phase. On a mechanistic level, withdrawal of either Asn or Gln stimulated the amino‐acid response (AAR) pathway, indicating that depletion of nonessential amino acids can induce AAR in this cell line. Compared to withdrawal of an essential amino acid, leucine (Leu), withdrawal of either Asn or Gln induced fewer changes in downstream effectors of mammalian target of rapamycin (mTOR) signaling involved in regulation of global protein synthesis. Global transcriptional analysis followed by pathway analysis revealed that the cultures experienced a down‐regulation of cell‐cycle progression, DNA replication and nucleotide biosynthesis in an E2F‐dependent manner, as well as a down‐regulation of lipid metabolism in a SREBP1/2‐dependent manner as a result of individual amino‐acid withdrawal. Timing and magnitude of observed phenotypic and transcriptional responses to amino‐acid withdrawal differed between essential (Leu) and nonessential (Asn and Gln) amino acids examined. Observed responses were similar in parental (CS9 and CHOK‐1) and two other antibody‐producing CHO cell lines, but the magnitude of the transcriptional response was both cell‐line and amino‐acid dependent. Overall, these results suggest that depletion of nonessential amino acids in cell culture plays a role in the onset of the stationary phase of production process and offer mechanistic insights into the observed growth attenuation phenotype. Biotechnol. Biotechnol. Bioeng. 2014;111: 965–979. © 2013 Wiley Periodicals, Inc.